Penyesuanian Diri Mantan Anak Didik Lembaga Permasyarakatan Palembang Kelas IIA Saat Kembali Ke Masyarakat Tahun 2012 - Ira Kusumawaty; Yunike Yunike; Sari Wahyuni (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2012)
Children and teenagers ever inhabit jail due to problems with the law, when entering impunity experiencing extreme enough changes in psychosocial problems, and this requires them to adapt to make the adjustments themselves so as not to get stuck back into illegal issues. This study aims to identify the adjustment of the eximprisoned person of jail in Palembang, especially when they return to society. The study also describes for the life of the subject in jail, especially their problems that will affect their adjustment process when returning to the community. This study uses a qualitative approach, and type of case studies, researchers conducted indepth interviews and observations on the subject meets the criteria as informants with their own researchers as key instrumen. Analysis has done through analysis of intercases and intracases to the data obtained. The results showed that problems faced by imprisoned person when out of jail consists of four aspects. Firstly, financial aspects that include the lack of employment imprisoned person. This is a major problem for the individual when it set foot in the outside world, because for the jail, imprisoned person accustomed to spend his days with lots of activity followed, accompanied by the availability of adequate means of support. Secondly, aspects of stigma, which led to the emergence of negative feelings labeled by society and shame on themselves imprisoned person. Thirdly, identity crisis, which resulted in individuals feel not confdent and not useful. Fourthly, relations, namely the emergence of strained relations with family members. Research focuses not only on the successful course, the role of the family should be increased, monitor of offcers after imprisoned person, fnished his sentence and the rehabilitation of the alcohol and drug users should be developed.